2006
DOI: 10.1271/bbb.70.348
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Typing of Miso and Soy Sauce Fermentation Yeasts,Candida etchellsiiandC. versatilis, Based on Sequence Analyses of the D1D2 Domain of the 26S Ribosomal RNA Gene, and the Region of Internal Transcribed Spacer 1, 5.8S Ribosomal RNA Gene and Internal Transcribed Spacer 2

Abstract: We analyzed sequences of the D1D2 domain of the 26S ribosomal RNA gene (26S rDNA sequence), and the region of internal transcribed spacer 1, 5.8S ribosomal RNA gene and internal transcribed spacer 2 (ITS sequence) of the miso and soy sauce fermentation yeasts, Candida etchellsii and Candida versatilis, in order to evaluate the usefulness of this sequence analysis for identification and typing of these two species. In the 26S rDNA sequence method, the numbers of base substitutions among C. etchellsii strains we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…All the strains were cultivated for 2 d at 30 C in 15 ml of YPG medium 3) or YPG + 5% NaCl medium at 120 rpm. DNA extraction was performed with PrepManÔ Ultra Sample Preparation Reagent (Applied Biosystems Japan, Tokyo) according to the manufacturer's protocol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All the strains were cultivated for 2 d at 30 C in 15 ml of YPG medium 3) or YPG + 5% NaCl medium at 120 rpm. DNA extraction was performed with PrepManÔ Ultra Sample Preparation Reagent (Applied Biosystems Japan, Tokyo) according to the manufacturer's protocol.…”
mentioning
confidence: 99%
“…Amplification and sequence analysis were performed according to a previous report. 3) 26S rDNA and ITS sequence analyses of Z. rouxii. The results of the 26S rDNA and ITS sequence analyses are shown in Table 1.…”
mentioning
confidence: 99%
“…The result showed that nucleotide substitutions in the domain do not exceed 1% among conspecific strains. Therefore, this method is effective for the identification and classification of yeasts [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Strains S2 and S8 from Group Nos.2 and 4 were related to Zygosaccharomyces bisporus NRRL Y-12626 (U72162, 100%) and to Pichia subpelliculosa NRRL Y-1683 (U74593, 99.8%), respectively ( Table 1). Genera of Candida, Pichia, and Zygosaccharomyces were typical salttolerant yeasts which form films at the surface of soy sauce and miso in fermentation tanks (Betts et al, 1998;Suezawa et al, 2006;Yajima et al, 1998). There have been few reports on the isolation of yeasts contaminating pickled plums, however, genera of Kloeckera, Candida, Pichia, and Debaryomyces have been isolated from Ume-zuke by Onda et al (1997).…”
Section: Introductionmentioning
confidence: 99%